Androgen Receptor Expression and Breast Cancer Survival: Results From the Nurses' Health Studies. (15th November 2018) - Kensler, Kevin H; Poole, Elizabeth M; Heng, Yujing J; Collins, Laura C; Glass, Benjamin; Beck, Andrew H; Hazra, Aditi; Rosner, Bernard A; Eliassen, A Heather; Hankinson, Susan E; Winer, Eric P; Brown, Myles; et al.
Abstract: Background: Hormone receptor signaling is critical in the progression of breast cancers, although the role of the androgen receptor (AR) remains unclear, particularly for estrogen receptor (ER)–negative tumors. This study assessed AR protein expression as a prognostic marker for breast cancer mortality. Methods: This study included 4147 pre- and postmenopausal women with invasive breast cancer from the Nurses' Health Study (diagnosed 1976–2008) and Nurses' Health Study II (1989–2008) cohorts. AR protein expression was evaluated by immunohistochemistry and scored through pathologist review and as a digitally quantified continuous measure. Hazard ratios (HR) and 95% confidence intervals (CI) of breast cancer mortality were estimated from Cox proportional hazards models, adjusting for patient, tumor, and treatment covariates. Results: Over a median 16.5 years of follow-up, there were 806 deaths due to breast cancer. In the 7 years following diagnosis, AR expression was associated with a 27% reduction in breast cancer mortality overall (multivariable HR = 0.73, 95% CI = 0.58 to 0.91) a 47% reduction for ER+ cancers (HR = 0.53, 95% CI = 0.41 to 0.69), and a 62% increase for ER− cancers (HR = 1.62, 95% CI = 1.18 to 2.22) ( P heterogeneity < .001). A log-linear association was observed between AR expression and breast cancer mortality among ER− cancers (HR = 1.14, 95% CI = 1.02 to 1.26 per each 10% increase in AR), although no log-linear association was observed among ER+ cancers. Conclusions: AR expression was associated with improved prognosis in ER+ tumors and worse prognosis in ER− tumors in the first 5–10 years postdiagnosis. These findings support the continued evaluation of AR-targeted therapies for AR+/ER− breast cancers.